Gas chromatography/negative chemical ionization mass spectrometry of transfluthrin in rat plasma and brain. (4th September 2017) - Hooshfar, Shirin; Mortuza, Tanzir B.; Rogers, Clinton A.; Linzey, Michael R.; Gullick, Darren R.; Bruckner, James V.; White, Catherine A.; Bartlett, Michael G.
Abstract : Rationale: Transfluthrin is a relatively non‐toxic rapid‐acting synthetic pyrethroid insecticide. It is widely used in household and hygiene products. A sensitive and accurate bioanalytical method is required for quantification of its concentration in plasma and its potential target organ, the brain for studies to assess its health effects and toxicokinetics in mammals. Methods: The samples were prepared by liquid–liquid extraction. Gas chromatography mass spectrometry (GC/MS) analysis was performed for the determination of transfluthrin in biological samples with an overall method run time of 15 min. Transfluthrin was quantified using selected‐ion monitoring (SIM) in the negative chemical ionization (NCI) mode. Chromatographic separation was achieved using a Zebron® ZB5‐MS GC column operating with 1 mL/min constant flow helium. Cis ‐Permethrin was used as the internal standard. Results: The method was validated to be precise and accurate within the linear range of 1.0–400.0 ng/mL in plasma and 4.0–400.0 ng/mL in brain homogenate, based on a 100 μL sample volume for both matrices. This method was applied to samples following administration of a 10 mg/kg oral dose to male adult rats. The plasma concentrations were observed to be 11.70 ± 5.69 ng/mL and brain concentrations 12.09 ± 3.15 ng/g when measured 2 h post‐dose. Conclusions: A rapid GC/NCI‐MS method was demonstrated to be sensitive, specific, precise and accurate for the quantification of transfluthrin in rat plasma and brain. The optimized method was successfully used to quantify the rat plasma and brain concentrations of transfluthrin 2 h after the oral dosing of Sprague–Dawley rats.